Incidencia de Kalotermes flavicollis (Fabricius)(Isoptera, Kalotermitidae) en tres especies del arbolado urbano de Sevilla - Noble, M.=700 1 Pavon, V.; Pradas, I.; Lopez, M.A.; Ocete, R.; Torrent, P.
(Es, En)
ilus., 8 ref.
Keywords: ISOPTERA; KALOTERMES; PLATANUS; PRUNUS CERASIFERA; ESPAÑA; PLATANO; CIRUELA